PENGARUH GAYA KEPEMIMPINAN, DAN MOTIVASI TERHADAP DISIPLIN KERJA KARYAWAN PADA PT BANK TABUNGAN NEGARA (PERSERO), Tbk CABANG DENPASAR - Diantari, Ida Ayu Putu Septy; Yuniari, Ni Made (E-Jurnal Manajemen, 2014)
Discipline is a factor which is very important to increase performance in a company. To develop discipline of employee in a company first we need to know what kinds of variables that relate to discipline . The purpose of this research is to find the influence of leadership type and motivation ti discipline. The research was conducted at Bank Tabungan Negara (Persero),tbk Branch Denpasar with a population 75  people and all of tehe population are choosed to be sample. The analysis technique used is simple linear regression. The result of this research are leadership type and motivation are influent work discipline, leadership type is particulary influent discipline, and motivation is particulary influent discipline toward the employees of PT Bank Tabungan Negara (Persero),tbk Branch Denpasar. To increase discipline realy Important for a company to pay attention about leadershipstyle . Therefore, fulltill the needs of the employes also really important to make discipline increase
Keywords: Leadership Style, Motivation, Discipline